Causal Inference Between Chronic Periodontitis and Chronic Kidney Disease: A Bidirectional Mendelian Randomization Analysis in a European Population - Yang, Jie; Chen, Tianyi; Zhu, Yahong; Bai, Mingxia; Li, Xingang (Frontiers in Genetics, 2021)
Background: Previous epidemiological studies have shown significant associations between chronic periodontitis (CP) and chronic kidney disease (CKD), but the causal relationship remains uncertain. Aiming to examine the causal relationship between these two diseases, we conducted a bi-directional two-sample Mendelian randomization (MR) analysis with multiple MR methods. Methods: For the casual effect of CP on CKD, we selected 7 single nucleotide polymorphisms (SNPs) specific to CP as genetic instrumental variables from the genome-wide association studies (GWAS) in the GLIDE Consortium. The summary statistics of complementary kidney function measures, i.e., estimated glomerular filtration rate (eGFR) and blood urea nitrogen (BUN), were derived from the GWAS in the CKDGen Consortium. For the reversed causal inference, 6 SNPs associated with eGFR and 9 with BUN from the CKDGen Consortium were included and the summary statistics were extracted from the CLIDE Consortium. Results: No significant causal association between genetically determined CP and eGFR or BUN was found (all p > 0.05). Based on the conventional inverse variance weighted method, one of seven instrumental variables supported genetically predicted CP being associated with a higher risk of eGFR (estimate = 0.019, 95% CI: 0.012 – 0.026, p < 0.001). Conclusions: Evidence from our bi-directional causal inference does not support a causal relation between CP and CKD risk and therefore suggests that associations reported by previous observational studies may represent confounding.